The Urgent Digitalization Asesmen Needs of Convention and Consulting In The Development of Conselor Competence - Nur Ainy Pricillia Susanti; Budi Purwoko; Elisabeth Christiana; Retno Tri Hariastuti (Universitas Muhammadiyah Enrekang, 2024)
Every human being living in any world needs what is called evolution. If we as humans are stagnant and don't want to follow the evolution of the times, we're going to get stuck with the development of the IPTEK, so that we are not out of date or out of age. So did the counsellor. Counselors are required to be able to understand the student in depth. A deep understanding of the students is called an assessment process. The realities in the field, the realities on the ground, the implementation of assessments in schools are not implemented to the maximum, besides requiring a sufficiently long mastery of knowledge, practice and synthesis, these conventional methods are irrelevant to the development of students who are very familiar with technology. Therefore, to address such challenges, it is possible to develop digital-based guidance and counseling assessment devices. The data obtained as many as 717 articles covering keywords “urgent digitalization assessment of guidance and counselling needs” and 146 articles that cover the keyword “counsellor competence” then found 15 research articles relevant to the urgency of digitalisation assessments of the need for mentoring and counseling in the development of the competence of counsellors, this is as a measure of evaluation. These results are important for a prospective Islamic consultant to enhance his professional competence in order to be able to compete with today's global challenges.